2021
DOI: 10.1186/s12916-021-02125-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of submucosal and subserosal approaches toward optimized indocyanine green tracer-guided laparoscopic lymphadenectomy for patients with gastric cancer (FUGES-019): a randomized controlled trial

Abstract: Background Application of indocyanine green (ICG) fluorescence imaging is effective in guiding laparoscopic radical lymphadenectomy for gastric cancer. However, the optimal approach for indocyanine green injection is controversial. Therefore, the objective of this study was aimed to compare the efficacy and ICG injection between the preoperative submucosal and intraoperative subserosal approaches for lymph node (LN) tracing during laparoscopic gastrectomy. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 37 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…Ultimately, the cost-effectiveness analysis performed in this study demonstrated how a subserosal injection can be a valid, cheaper solution, particularly considering the workload reduction experienced by endoscopists for tumors other than cT1. In conclusion, the authors did not find any difference in the lymph node-related outcomes between the two methods, with better patient satisfaction and cost effectiveness in favor of subserosal injection; however, they underlined how similar studies should be conducted by analyzing data from neoadjuvated patients ( 59 ).…”
Section: Lymph Nodesmentioning
confidence: 90%
See 1 more Smart Citation
“…Ultimately, the cost-effectiveness analysis performed in this study demonstrated how a subserosal injection can be a valid, cheaper solution, particularly considering the workload reduction experienced by endoscopists for tumors other than cT1. In conclusion, the authors did not find any difference in the lymph node-related outcomes between the two methods, with better patient satisfaction and cost effectiveness in favor of subserosal injection; however, they underlined how similar studies should be conducted by analyzing data from neoadjuvated patients ( 59 ).…”
Section: Lymph Nodesmentioning
confidence: 90%
“…In a cohort study, Zhong et al presented pooled data from the previously cited FUGES-012 trial ( 23 ) and FUGES-019 trial ( 59 ). The authors confirmed a higher number of retrieved lymph nodes and a reduction in the non-compliance rate of D2 lymphadenectomies performed using ICG.…”
Section: Lymph Nodesmentioning
confidence: 99%
“…In colo-rectal or gastric cancer, after the peritumoral injection of ICG, the dye follows the lymphatic pathways and colors the lymph nodes it finds along the collectors. The presence of cancer cells within the metastatic lymph node does not seem to decrease the intensity of staining [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…3c ). The same surgical team further compared the performance of sub-mucosal and sub-serosal injection of ICG [ 74 ]. A total of 259 patients were enrolled in this per-protocol analysis.…”
Section: Lymphatic Fmi Imagingmentioning
confidence: 99%